Gastroduodenal motility disorders. Issue 6 (November 2018) - Tack, Jan; Van den Houte, K.; Carbone, Florencia
Abstract : Purpose of review: This review summarizes recent progress in the epidemiology, pathophysiology and treatment of gastroduodenal motility disorders with an emphasis on functional dyspepsia and gastroparesis. Recent findings: Pathophysiological research has focused on the association of delayed emptying and impaired accommodation with symptom pattern. Studies also confirmed the presence of altered mucosal integrity and low-grade immune activation in the duodenum in functional dyspepsia, while changes in numbers of interstitial cells of Cajal and myenteric neurons were confirmed in gastroparesis. Treatment advances in gastroparesis include new prokinetics such as the ghrelin receptor agonist relamorelin and the antiemetic agent aprepitant. The efficacy and use of neuromodulators were reviewed and new management guidelines for functional dyspepsia were published. Summary: Pathophysiological research has focused on cellular changes in gastroparesis and gastroduodenal motility disorders. New treatments include relamorelin and aprepitant for gastroparesis.